The effect of IFRS application on turnover figures of Romanian companies - Inesa Tofănică; Emil Horomnea (CES Working Papers, 2020)
Romanian accounting system had different development stages. The last one started when Romania accessed the European Union. As the EU member states had the obligation to issue financial statements of the listed companies using International Financial Reporting Standards (IFRS), Romania was no exception. As IFRS are different from national accounting regulations, it is expected that the reported turnover will be different under IFRS regulations compared to the national ones. In this paper we study to which extent the IFRS implementation has changed the accounting figures on turnover declared by Romanian listed companies. As the results show us, the majority of the companies have been neutral in what concerns the IFRS implementation, i.e., the reported turnover does not differ very much when different accounting regulations were applied (the national ones and the IFRS).
Keywords: 330; European Union; IFRS implementation; Gray index